Civil-Military Relations in Pakistan (2018–2023): Analyzing Political Instability and Institutional Power Shifts - Ali Nawaz Soomro; Dr. Dilawar Khan; Dr. Asif Salim (Dialogue Social Science Review (DSSR), 2025)
This research thesis critically examines the dynamics of civil-military relations in Pakistan between 2018 and 2023, a period marked by heightened political instability and significant institutional power shifts. The study investigates how the balance of power between civilian governments and the military establishment evolved during this time, particularly under the Pakistan Tehreek-e-Insaf (PTI) government and in the wake of its subsequent removal. The research also explores how institutional interventions, judicial influence, and the role of security agencies impacted democratic governance and civilian supremacy. Using a qualitative approach grounded in political theory and empirical data, the thesis identifies recurring patterns of military dominance in policy-making, electoral engineering, and crisis management. It highlights key events such as the PTI-military alliance and its eventual fallout, opposition-led movements, and the increasing involvement of the judiciary and intelligence agencies in political affairs. These factors contributed to institutional fragmentation, public mistrust, and weakened democratic norms. The study concludes that despite formal democratic structures, Pakistan continues to experience an imbalance in civil-military relations, with the military wielding disproportionate influence. The thesis recommends structural reforms, constitutional safeguards, and greater civilian capacity-building to establish a sustainable democratic framework. This work contributes to the broader discourse on democratization, civil supremacy, and political stability in transitional states.